جائحة كورونا والاهتزازات الامبريقية لحوكمة الصحة العالمية - شملال, وليد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
في محاولة بحثية متعددة المستويات نعالج تقويميا ونفحص تجريديا مدى تأثير جائحة كورونا على حوكمة الصحة العالمية، وخلق نمطية أكثر لفعالية الترتيبات المؤسسية الصحية في ضبط لهذه الجائحة العابرة للحدود، من خلال مراجعتنا لأهم النماذج المفسرة للاختلالات التي تعرقل اصلاح المنظومة الصحية العالمية، خاصة عن مدى جاهزية هذا القطاع في تلبية الحد الأدنى من الرعاية الصحية للدول النامية. تم الاعتماد على خطة منتظمة أمكن من خلالها الاجابة عن اشكالية الدراسة وفحص الافتراض العلمي للتحقق من مدى تأثير جائحة كورونا على حوكمة الصحة العالمية، وتعرية الخطابات المعيارية أمام الجهود التي تعرقل مجهود الاصلاح. In a multi-tiered research effort, we are addressing orthographically and gradually examining the impact of the Corona pandemic on global health governance, and creating a more typical of the effectiveness of health institutional arrangements in controlling this cross-border pandemic, through our review of the most important and explained models of imbalances that impede the reform of the global health system, particularly on the readiness of the sector to meet the minimum level of health care of developing countries It was based on a systematic plan that could answer the problems of the study and examine the scientific hypothesis to ascertain the impact of the Corona pandemic on global health governance, and to strip normative rhetoric in the face of efforts to impede the reform effort.